Green synthesis of silver nanoparticles by using various extracts: a review. Issue 5 (24th August 2020) - Ijaz, Mohsin; Zafar, Maria; Iqbal, Tahir
Abstract: Recently, nanotechnology has emerged as a tool for the development in the biological synthesis of noble metal nanoparticles. Among other conventional synthesis methods, biological synthesis methods have received great significance due to cost-effective and less hazardous nature which is due to the presence of plentiful as well as diversified biomolecules acting as capping and reducing agents. Biosynthesized silver nanoparticles (Ag NPs) manifest potential applications in several fields because of its safe and environment friendliness. Reported researches on the green synthesis of Ag NPs using different parts of stem, fruits, and seeds has been summarized along with the impact on the morphological properties. This review is important to find a way toward the cheaper, environmentally friendly and controlled synthesis of Ag NPs hence is of special concern.